Struktur Sisik Sayap Kupu-Kupu Superfamili Papilionoidea (Lepidoptera) - Astrid Sri Wahyuni Sumah (Universitas Hasanuddin, 2019)
The structure of wing scales in four species of papilionid butterflies were investigated. The aim of this study was to determine the differences of wing scales structure from four species butterflies in Superfamily Papilionoidea. Small fragments of wings vein M1 and M2 were cut and observed using Scanning Electron Microscopy (SEM). The wing scales had two types, i.e. rectangular and triangular. Microstructure of wings scales also had many forms consist with window, crossribs, and ridges. All scales of the wing of butterflies observed had different forms (scales, microstructures, and serrations), eventhough the point of viewd were the same. Only Catopsilia scylla had two types scales and Arhopala araxes had different forms of microstructures.